Cobalt-Catalyzed Reductive Heck Cyclization Using Water as Hydrogen Donor to Access Oxindoles - Sun, Li-Dong; Xiao, Qian; Li, Sanliang; Zhong, Jian-Ji (Synlett, 2025)
An efficient cobalt-catalyzed intramolecular reductive Heck reaction using water as hydrogen donor for the synthesis of valuable 3,3-disubstituted oxindoles from 2-halo-N-arylacrylamides is described. The approach features operational simplicity and high functional group tolerance. Importantly, when the reaction was performed in D2O, the deuterated oxindoles could be rapidly accessed in a facile and low-cost manner.
Keywords: cobalt catalysis; reductive Heck cyclization; water, oxindoles; deuterium reaction